2014
DOI: 10.3233/jad-140354
|View full text |Cite
|
Sign up to set email alerts
|

Rates of Formal Diagnosis in People Screened Positive for Dementia in Primary Care: Results of the DelpHi-Trial

Abstract: The diagnosis rate of dementia in German primary care (40%) is well within the range of the international data (20-50%). The results emphasize the need for action to enhance recognition and differential diagnosis of dementia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
71
0
14

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 95 publications
(92 citation statements)
references
References 35 publications
7
71
0
14
Order By: Relevance
“…In Europe and the US less than 50% of people with clinical dementia receive a formal diagnosis of dementia in primary care. 56 With limited access to specialized care for the majority of cases and countries the penetration of validated biomarkers into routine care may leverage specialized care resources to provide broader access to diagnosis and treatment options for the entire population of people with manifest symptoms of dementing neurodegenerative disorders. This design is replaced by prospective longitudinal repository studies, where the biomarker is measured at baseline in MCI patients, and Alzheimer's disease status ascertained at follow-up.…”
Section: 6mentioning
confidence: 99%
“…In Europe and the US less than 50% of people with clinical dementia receive a formal diagnosis of dementia in primary care. 56 With limited access to specialized care for the majority of cases and countries the penetration of validated biomarkers into routine care may leverage specialized care resources to provide broader access to diagnosis and treatment options for the entire population of people with manifest symptoms of dementing neurodegenerative disorders. This design is replaced by prospective longitudinal repository studies, where the biomarker is measured at baseline in MCI patients, and Alzheimer's disease status ascertained at follow-up.…”
Section: 6mentioning
confidence: 99%
“…Reliable figures are difficult to determine because the majority (about 60%) of communitydwelling PWD in Germany is not formally diagnosed with dementia [9] and general practitioners (GP) are even less likely to recognize dementia when patients live alone [10].…”
Section: Introductionmentioning
confidence: 99%
“…These have been applied in healthcare research close to routine care and have shown their impact on routine care; however, there are healthcare-specific challenges when applying scientific methods in routine care, which are briefly described. [30] oder ergänzt frühere ökonomische Analysen der Kosten der Demenz [31], aber weist auch auf andere Problemfelder hin, z. B. dass ca.…”
Section: German Study On Ageing Cognition and Dementiamentioning
confidence: 99%